EVERYDAY DIGITAL PRACTICES AND SOCIAL MEANING: A SOCIOLOGICAL ANALYSIS OF TECHNOLOGY USE IN URBAN COMMUNITIES - wijaya, wijaya; Akbar , Ali; Rahimi , Ramin (Yayasan Adra Karima Hubbi, 2026)
Digital technologies have become embedded in the routines of urban life, reshaping how individuals interact, coordinate activities, and construct social meaning. Sociological analyses that focus primarily on macro structures often overlook routine practices through which technology becomes socially significant. This study aims to examine everyday digital practices in urban communities and to analyze how routine technology use contributes to the production of social meaning, interactional norms, and perceptions of belonging. The research employs a qualitative sociological design, combining in-depth interviews, observation of everyday practices, and analysis of digital artifacts to capture lived experiences of urban technology use. The findings indicate that everyday digital practices function as socially meaningful actions rather than neutral technical behaviors. Routine engagement with smartphones, social media, and digital service applications shapes expectations of availability, responsiveness, and social visibility, reinforcing hybrid forms of online and offline interaction. Digital practices are shown to strengthen social coordination while simultaneously reproducing subtle forms of exclusion within urban settings. The study concludes that social meaning in urban communities is increasingly produced through habitual digital practices that organize everyday life. Understanding technology use as a routine social practice provides critical insight into contemporary urban social transformation and underscores the relevance of sociological perspectives in digital society research.